Development discourses of the low human development index : countries in UN post-2015 discussion - Leskinen, Kati (2015)
This study is about development discourses and agents of the countries with low Human Development Index (HDI) in Africa. It is based on six UN Post-2015 national consultations. These six nations are Burkina Faso, the Democratic Republic of Congo, Ethiopia, Mozambique, Liberia and Zambia. The criteria of data selection involve the level of HDI, language, format of the report and geographical location. The idea about development as discursive constructed social reality is at the focus of theoretical framework. The method is Discourse Analysis (DA) with some Foucauldian characteristics. The research questions are: What kind of specific development discourses and agentive roles are there in policy papers in Post-2015 discussion? What are the main discourses of development according to low-HDI nations? How do low-HDI nations in Africa perceive the concept of development and its discursive representations? The discourses found from the data are labelled as UN, Nation State and Services. The theme of agency is quite cross-cutting in the discursive regime. Thus it is given its own chapter with analysis of discursive roles found in the papers. The roles found are labelled as facilitator, consultant, consultee, beneficiary and responsible. Different data-driven discourses as well as the analysis of agency create the basis for synthetization and identification of broader development discourses. These broader development discourses are identified as Development Path and Power of International Development Agenda.